P Profil Penggunaan Antibiotika di Puskesmas Hantakan dan Profil DAGUSIBU Antibiotika di Desa Hantakan dan Desa Alat - Rina Saputri; Ali Rakhman Hakim (LPPM Universitas Sari Mulia, 2021)
Background : The used of antibiotics in Indonesia continues to increase, but not accompanied by good knowledge regarding the used of these antibiotics so that they have a high risk of causing antibiotic resistance. Objective : Knowing the profile of the use of Antibiotics in Puskesmas Hantakan and knowing the profile of DAGUSIBU antibiotics in Hantakan and Alat Villages. Method : This type of research is descriptive research with survey methods for the last 5 months from October 2020 to February 2021. The survey was also carried out directly to the respondents of the Hantakan Village RT.01 - RT.06 and in Village Alat RT.01 - RT.04. Results : The used of antibiotics at Puskesmas Hantakan is one of the top 10 drugs that are often prescribed. The type of antibiotic that is most widely prescribed is Amoxicillin. DAGUSIBU's profile on respondents shows that the majority of respondents get antibiotics from stalls, use antibiotics to treat various diseases, take antibiotics not according to intervals, stop antibiotics if they feel that conditions have improved, and still keep antibiotics in stock and dispose of antibiotics in an inappropriate way. Conclusion : Amoxicillin is a type of antibiotic that is most widely prescribed in Puskesmas Hantakan. The use of antibiotics without a doctor's prescription in Hantakan and Alat Villages is still high. The proper management of antibiotics among respondents in the Village of Hantakan and Alat was still low.